Development of Human Resources at The Regional Human Resources Development Agency of Palu City - Jisman Jisman; Daswati Daswati; Abdul Rivai; Nasir Mangngasing (Khazanah Sosial, 2025)
This study aims to determine how the development of civil servant resources at the Palu City Regional Human Resources Development Personnel Agency. The type of research used is descriptive qualitative. The type of data uses primary data and secondary data. Data collection techniques, carried out through observation, interviews, and documentation. The informant drawing technique uses purposive. Data analysis used is the Miles, Huberman and Saldana model, namely data collection, data presentation, data condensation and conclusion drawing. Based on the results of the research that has been done, there are recommendations that can be given to improve the effectiveness of civil servant resource development at the Palu City Regional Human Resources Development Personnel Agency. These recommendations are compiled by considering field findings on the dimensions of training, education, and development according to Nadler's theory (1990), Increasing the Frequency and Equity of Training needs to increase the number of technical training and technical guidance every year, with an even distribution to all ASN so that each employee has the same opportunity to develop skills, Preparation of More Relevant Training Materials Training materials should be compiled based on job needs analysis (training needs analysis) so that the training output directly impacts performance improvement according to each employee's duties. Expanding Access to Formal and Non-Formal Education: Regional governments are expected to increase budgetary and policy support for civil servants (ASN) to participate in further studies, seminars, and workshops, so that strategic competency development can be equitably distributed. Strengthening the Career Development System: Talent pools, job rotations, and leadership development programs need to be expanded to encompass more employees, so that they are not solely focused on specific individuals but provide equal opportunities for all potential ASN. Measurable Post-Program Evaluation at the Civil Service Agency: Human Resource Development needs to establish a post-training, education, and development evaluation mechanism, both in terms of performance and employee behavioral changes, to ensure that implemented programs truly deliver the desired impact.